حالة سكان العالم لعام2023 - United Nations Population Fund (United Nations, 2024)
The State of World Population report 2023 will discuss the milestone of 8 billion recently reached by the human population and the narratives surrounding population change. We will look in particular at discourses which put forward ideas of 'too many' or 'too few' people and at the harm this can cause women and girls whose reproductive choices are on the line.